Night syncope: a case report. Issue 2 (26th December 2016) - Loumaye, Léopold; Blommaert, Dominique
Key Clinical Message: "Idiopathic" ventricular fibrillations are rare and are estimated between 5% and 10% of survivors of hospital cardiac arrest, for at least some of them have as origin, a trigger in the Purkinje fibers. Interventional therapy could be an effective, long‐lasting solution for these recurrent malignant arrhythmias and should be considered. Abstract : "Idiopathic" ventricular fibrillations are rare and are estimated between 5% and 10% of survivors of hospital cardiac arrest, for at least some of them have as origin, a trigger in the Purkinje fibers. Interventional therapy could be an effective, long‐lasting solution for these recurrent malignant arrhythmias and should be considered.